"Syria is Our Mom, UK is Like Aunty": The Psychosocial Experiences of Acculturation in Syrian Refugees. (17th June 2022) - Asmal-Lee, Mujahid; Liebling, Helen; Goodman, Simon
Abstract: In response to the Syrian Civil War, the British Government pledged to resettle 20, 000 Syrian refugees by 2020. However, refugee integration can be traumatic. Existing literature has gaps encompassing the 'lived experiences' of Syrian refugees specifically. This study used semi-structured interviews and Interpretative Phenomenological Analysis to explore six Syrian refugees' acculturation in the UK. Three superordinate themes were developed: Living with Loss, Experiencing a New Life, and The Dissonance of Integration: Belonging and Not Belonging. Syrian refugees' losses impacted their integration. Arrival was experienced as an overwhelming re-birth for some, yet despite their new life, refugees' integration could not escape past traumas. Syrian refugees' integration encompassed degrees of belonging, racism, and Islamophobia. Experiences were affected by nurture, support, and connection with state structures, the host society and other refugees. Services and professionals would benefit from understanding refugees' needs through cultural curiosity, sensitivity, and trust, to avoid exacerbating trauma. Policy recommendations include supporting refugees into meaningful employment and legal support for family reunification. Refugee voices and expertise should be considered in all aspects of integration. Findings have implications for models of integration particularly regarding the role of identity, employment, and how refugees' experiences relate to what models view as 'integration'.